2011
DOI: 10.1002/mrm.22999
|View full text |Cite
|
Sign up to set email alerts
|

Tumor imaging using hyperpolarized 13C magnetic resonance spectroscopy

Abstract: Dynamic nuclear polarization is an emerging technique for increasing the sensitivity of magnetic resonance imaging and spectroscopy, particularly for low-g nuclei. The technique has been applied recently to a number of 13 C-labeled cell metabolites in biological systems: the increase in signal-to-noise allows the spatial distribution of an injected molecule to be imaged as well as its metabolic product or products. This review highlights the most significant molecules investigated to date in preclinical cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
357
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 236 publications
(362 citation statements)
references
References 103 publications
(247 reference statements)
4
357
1
Order By: Relevance
“…41 While a variety of Ln(iii) complexes have numerous biomedical applications, particularly in contrast-enhanced MRI, 45 only Gd 3+ and Ho 3+ have been studied extensively as beneficial doping agents in 13 C dissolution DNP. [35][36][37][38] This in part takes precedent from a previous preliminary study which has shown that only Gd 3+ and Ho 3+ ions have beneficial effects on 13 C DNP, while the other Ln(iii) ions appear to have no apparent effect on 13 C DNP enhancements for trityldoped samples. 37 We would like to note that the measurements in the aforementioned previous DNP study on using lanthanide ions 37 were not really extensively optimized in terms of concentration dependence and the fact that the optimum DNP microwave frequency could shift with lanthanide doping.…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…41 While a variety of Ln(iii) complexes have numerous biomedical applications, particularly in contrast-enhanced MRI, 45 only Gd 3+ and Ho 3+ have been studied extensively as beneficial doping agents in 13 C dissolution DNP. [35][36][37][38] This in part takes precedent from a previous preliminary study which has shown that only Gd 3+ and Ho 3+ ions have beneficial effects on 13 C DNP, while the other Ln(iii) ions appear to have no apparent effect on 13 C DNP enhancements for trityldoped samples. 37 We would like to note that the measurements in the aforementioned previous DNP study on using lanthanide ions 37 were not really extensively optimized in terms of concentration dependence and the fact that the optimum DNP microwave frequency could shift with lanthanide doping.…”
Section: Introductionmentioning
confidence: 77%
“…1 As a result of relatively low gyromagnetic ratio γ of nuclear spins, the spin population difference between Zeeman energy states, quantified by the polarization, can be quite miniscule. This is particularly prominent in the case for low-γ nuclei such as 13 C or 15 N. Consequently, NMR under these conditions often requires a large number of scans in order to achieve adequate signal-to-noise. While NMR is relatively insensitive, electron paramagnetic resonance (EPR), a similar technology, does not suffer from this problem.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations